Efficacy of Nagaradi Vati In the Management of Mutrashmari w.s.r. to Urolithiasis (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: Mutrashmari is one of the most common and distressing malady among urinary disorders. The urological diseases like Ashmari, Mutrakrichra, Mutraghata, Prameha are the ailment causing suffering to human health since ancient age. Urolithiasis is still a mysterious even after extensive research in urology because the cause and mechanism of stone formation is still uncertain. Urolithiasis formation is a complex process which involves crystalloid and colloids. Ayurveda has a unique concept of breaking the stone by using the Ashmari-bhedana and Mutral drugs. Objective: An effort was made to evaluate the efficacy of Nagaradi Vati in Mutrashmari patients. The main aim of this study was inclined towards the disintegration, dissolution, dislodgement and expulsion of urinary stones. Therefore, trial formulation which has Ashmari-bhedana and Mutral properties has been selected for the study. Methods: The trial drug is having anti-inflammatory, diuretic and litholytic, antilithiatic properties. Total 30 patients were randomly selected and treated with Nagaradi Vati in a dose of 500 mg, thrice daily after food for duration of 90 days. Result: The result of trial drug in pain, tenderness, burning micturition, size and number of calculi was statistically highly significant. In pyuria and haematuria result was statistically significant. Conclusion: Management of Mutrashmari by Nagaradi Vati has given significant improvement in the sign, symptoms and size of stone. It has paved new way of treatment, which is effective and with no adverse effect.